Inventory Management Optimization via Forecasting, IT Infrastructure, Technology Integration, and Supply Chain Resilience: Exploring the Mediating Role of Decision-Making Effectiveness - Mohanad Mohammed Sufyan Ghaleb; Zilola Shamansurova (Decision Making: Applications in Management and Engineering, 2025)
Inventory management is integral to ensure that products are available at the right time which enhance the company’s operational efficiency. To optimize this, the study objective was to test the impact of IT infrastructure, demand forecasting, technology integration, and supply chain resilience on inventory management with the mediating effect of decision-making effectiveness of manufacturing companies. Cross-sectional quantitative data were collected from 260 employees of manufacturing companies using a convenient sampling technique. Hypothesis results show that IT infrastructure, demand forecasting, technology integration, and supply chain resilience have a positive and significant impact on inventory management. Decision-making effectiveness also significantly increases inventory management. Decision-making effectiveness also mediates among IT infrastructure, demand forecasting, technology integration, supply chain resilience, and inventory management of manufacturing companies. The study results indicated that increasing technological awareness and supply chain resilience could significantly improve inventory management in manufacturing companies. Furthermore, strengthening the effectiveness of decision-making also strengthens these impacts through serving as a key mediating mechanism. This study uniquely integrates multiple technological and strategic factors into one model, highlighting the mediating role of decision-making effectiveness in improving inventory management.